Trajectories into famine: observations of patterns and implications for prevention - Daniel Maxwell; Matthew Day; Merry Fitzpatrick; Paul Howe; Peter Hailey; Anu Atre; Alex de Waal (Food Policy, 2026)

Hydrogeochemical processes driving elevated Arsenic and Fluoride in the Texas Gulf Coast Aquifer - Hailey N. Goodwin; Taehyun Roh; Reid Buskirk; D. Kirk Nordstrom; Franco Marcantonio; Peter S.K. Knappett (Applied Geochemistry, 2026)

High‐resolution analysis of sediments from Eighteen Mile Swamp (eastern Australia) records its transition from a fluctuating coastal lagoon to stable freshwater swamp - Jonathan C. Marshall; John Tibby; Patrick Moss; Hailey Martin; Allen Gontz; Annie Lau; Geraldine E. Jacobsen; Haidee Cadd; Patricia S. Gadd; Peter Negus; GLENN B. Mcgregor; Harald Hofmann; et al. (Journal of Quaternary Science, 2025)
This research documents the paleoenvironmental evolution of Eighteen Mile Swamp on North Stradbroke Island (Minjerribah), Australia, from oscillating coastal lagoon into stable freshwater swamp over the last ca. 1600 years. We analyzed multiple sediment cores via physical description, acid sulfate soil assays, particle size analysis, diatom and pollen assemblages, photosynthetic pigment content, and Itrax XRF spectrometry, alongside ground‐penetrating radar cross‐sections. This provided a detailed ecological, geochemical and chronological framework, derived from radiocarbon, Pu and 210 Pb dating, for the wetland's evolution. Results indicate spatial complexity in the timing of a pronounced shift in sedimentary conditions between ca. 300 and 1000 years ago, from estuarine mud to freshwater peat, marked by abrupt chemical and ecological changes. Unexpectedly, there were at least three and potentially many periods of dominant freshwater influence within the primarily estuarine phase, suggesting episodic estuarine closure and freshening by groundwater influx. Results provide critical insights into the complex response of subtropical wetland systems to environmental change, emphasizing the importance of interdisciplinary approaches in understanding both sedimentologic and geomorphic responses in coastal wetlands, and their potential vulnerability to future climate change. The study of Eighteen Mile Swamp is significant as it provides a detailed paleoenvironmental reconstruction that documents the wetland's evolving nature over the past two millennia. This research highlights the importance of understanding historical responses of wetlands to environmental changes, which helps inform their current and future management, conservation and restoration efforts, particularly in the context of climate change and human impacts. This study also serves as a tribute to the late Lynda Petherick, acknowledging her contributions in this field.

Using the household hunger scale to improve analysis and classification of severe food insecurity in famine-risk conditions: Evidence from three countries - Daniel Maxwell; Guhad Adan; Peter Hailey; Matthew Day; Stephen B.J. Odhiambo; Lilian Kaindi; James Njiru; Aishwarya Venkat; Anastasia Marshak (Food Policy, 2023)

Serotonin 5-HT1B receptors mediate the antidepressant- and anxiolytic-like effects of ventromedial prefrontal cortex deep brain stimulation in a mouse model of social defeat - Esther Silk; Mustansir Diwan; Thallita Rabelo; Hailey Katzman; Ana Carolina P. Campos; Flavia Venetucci Gouveia; Peter Giacobbe; Nir Lipsman; Clement Hamani (Psychopharmacology, 2022)

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Steady-state cerebral blood flow regulation at altitude: interaction between oxygen and carbon dioxide - Hailey C. Lafave; Shaelynn M. Zouboules; Marina A. James; Graeme M. Purdy; Jordan L. Rees; Craig D. Steinback; Peter Ondrus; Tom D. Brutsaert; Heidi E. Nysten; Cassandra E. Nysten; Ryan L. Hoiland; Mingma T. Sherpa; et al. (European Journal of Applied Physiology, 2019)